2019
DOI: 10.1177/1358863x19867393
|View full text |Cite
|
Sign up to set email alerts
|

Healthy diet and fiber intake are associated with decreased risk of incident symptomatic peripheral artery disease – A prospective cohort study

Abstract: Peripheral artery disease (PAD) is caused by atherosclerosis and associated with an increased risk of leg amputation, cardiovascular disease, and death. A healthy diet has been shown to reduce the risk of cardiovascular events, but relationships between diet, fiber intake, and incidence of PAD are virtually unknown. The aim was to investigate the long-term impact of diet on the development of PAD among 26,010 middle-aged individuals in the prospective Malmö Diet and Cancer study (MDCS). Data on dietary intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The association between fiber intake and reduced risk of incident peripheral atherosclerotic occlusive disease [6] was further strengthened by the present study finding on the composite endpoint ACVD. Soluble fiber prolongs the emptying of the stomach and food transit time by forming a gel, lowering postprandial blood glucose and lipid increase [21].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The association between fiber intake and reduced risk of incident peripheral atherosclerotic occlusive disease [6] was further strengthened by the present study finding on the composite endpoint ACVD. Soluble fiber prolongs the emptying of the stomach and food transit time by forming a gel, lowering postprandial blood glucose and lipid increase [21].…”
Section: Discussionsupporting
confidence: 71%
“…A high diet quality was associated with lower incidence of cardiovascular events in terms of myocardial infarction or ischemic stroke with follow up to 2008 in the Malmö Diet and Cancer Study (MDCS) [5]. A healthy diet and adherence to recommended levels of fiber intake were associated with a reduced risk of incident peripheral artery disease in MDCS [6], whereas no association was found between diet quality and incident carotid artery disease [7], but this study was probably underpowered. Current smoking, low diet quality and low physical activity level were associated with atherothrombotic ischemic stroke in MDCS [8].…”
Section: Introductionmentioning
confidence: 82%
“…The main finding in this population-based prospective cohort study with a median follow-up of 21.8 years was a trend toward a protective effect of adherence to recommended levels of fruit and vegetable on risk of incident CAD. Similarly, fruit and vegetables have been found to reduce the incidence of peripheral artery disease [12], CV events [13], and abdominal aortic aneurysm [14] in the same cohort. Only one other prospective longitudinal cohort study was found to specifically address the association between intake of vegetables and CAD, which showed an inverse association of vegetable nitrate intake with carotid atherosclerosis and ischemic cerebrovascular disease in older women after a follow-up of 14.5 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study involved 26 010 middle-aged men and over 20 years of follow-up. The results indicated that individuals who consumed the recommended intakes of fibre, fruit and vegetables had significantly lower risk of developing peripheral artery disease (Kulezic et al 2019). In another study, the association between CVD risk and dietary fibre intake was examined in a cohort of women.…”
Section: Cardiovascular Diseasementioning
confidence: 99%